The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.15448/1980-8623.2019.1.29275
|View full text |Cite
|
Sign up to set email alerts
|

Authoritative school climate and peer victimization among Brazilian students

Abstract: According to the Authoritative School Climate theory, a school environment perceived with high levels of support and disciplinary structure can be a protective factor against violence. Therefore, the current study aimed to understand how support and disciplinary structure affected peer victimization among Brazilian students. Participants were 420 students from Brazil, between 7 and 14 years old (mean=10.02; S.D. = .91); 51.5% of the participants were boys. Measures were obtained from a self-report questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…When there is more support, student virtues of social responsibility are even more connected to diminishing classroom aggression. The significant interactions between support and structure are consistent with the authoritative school model and highlight the importance of holding children to a high interpersonal standard, but giving them all the supportive relationships and explicit socioemotional instruction to help them achieve those standards (Amaral et al, 2019;Bear et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…When there is more support, student virtues of social responsibility are even more connected to diminishing classroom aggression. The significant interactions between support and structure are consistent with the authoritative school model and highlight the importance of holding children to a high interpersonal standard, but giving them all the supportive relationships and explicit socioemotional instruction to help them achieve those standards (Amaral et al, 2019;Bear et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…Positive perceptions of school climate have been consistently linked to fewer behavioral and emotional problems in middle childhood (Klein et al, 2012;Reaves et al, 2018;Wang & Dishion, 2012) and are associated with higher levels of school safety and lower frequency of peer victimization and aggression (e.g., Amaral et al, 2019;Corrigan et al, 2010;Gage et al, 2014;Gendron et al, 2011;Leadbeater et al, 2015). The importance of school climate and the ways that students conceptualize it appear similar across cultures (see LaSalle, 2018).…”
Section: The Influence Of School Climatementioning
confidence: 99%
See 2 more Smart Citations
“…The same authors cite results that show a significant impact of a negative school climate on increasing peer violence at school. Research conducted by Amaral et al (2019) also showed that student support (related to student's experience with teachers and other school professionals, and perceived as welcoming, inclined to help and respectful) was a negative predictor for reports of victimization. Similar results were obtained by Berkowitz et al (2015), on a sample of 53,946 fifth-and eighth-grade students in public schools in Israel, indicating significant negative correlation between school violence and positive student-teacher relationship.…”
Section: Introductionmentioning
confidence: 96%